Secondary Distribution of HIV Self-Testing Kits to Social and Sexual Networks of PLWH in KwaZulu-Natal, South Africa. A Brief Report - Sithole, Nsika; Koole, Olivier; Sausi, Kombi; Krows, Meighan; Schaafsma, Torin; Van Heerden, Alastair; Shahmanesh, Maryam; van Rooyen, Heidi; Celum, Connie; Barnabas, Ruanne V.; Shapiro, Adrienne E. (Frontiers in Public Health, 2022)
Background: To reach 95% of persons living with HIV (PLWH) knowing their HIV status, alternative testing approaches such as HIV self-testing (HIVST) and secondary HIVST kit distribution are needed. We investigated if secondary HIVST kit distribution from male and female PLWH in South Africa would successfully lead to their contacts testing for HIV and linking to care if positive. Methods: Male and female PLWH participating in an HIV treatment trial between July and November 2018 in KwaZulu-Natal, South Africa were offered participation as “HIVST kit distributors” in a pilot of secondary distribution of HIVST kits to give to sexual partners and social networks. The characteristics of volunteer distributors, proportion of HIVST recipients who reported their results, and linkage to care among those who tested positive using HIVST were assessed. Results: Sixty-three participant kit distributors accepted kits to disperse to contacts, of whom 52% were female, median age was 34 years, 84% reported 1 sexual partner and 76% did not know their partner’s HIV status. HIVST kit distributors took 218 kits, with 21% reporting they intended to give the kits to a sexual partner. A total of 143 HIVST recipients reported their HIVST results; 92% reported their results were negative, 11 recipients reported positive results and 1 HIVST-positive recipient was linked to HIV care. Conclusion: Secondary distribution of HIVST to social networks and sexual partners from South African PLWH is feasible, with two thirds of contacts reporting use of the HIVST kits. Additional support is necessary to facilitate linkage to care.